2000
DOI: 10.1242/dev.127.11.2259
|View full text |Cite
|
Sign up to set email alerts
|

The paired homeobox gene Uncx4.1 specifies pedicles, transverse processes and proximal ribs of the vertebral column

Abstract: The axial skeleton develops from the sclerotome, a mesenchymal cell mass derived from the ventral halves of the somites, segmentally repeated units located on either side of the neural tube. Cells from the medial part of the sclerotome form the axial perichondral tube, which gives rise to vertebral bodies and intervertebral discs; the lateral regions of the sclerotome will form the vertebral arches and ribs. Mesenchymal sclerotome cells condense and differentiate into chondrocytes to form a cartilaginous pre-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(17 citation statements)
references
References 43 publications
3
13
1
Order By: Relevance
“…Table 2 ). Human UNCX encodes a homeobox transcription factor whose mouse homolog is implicated the development of the axial skeleton and in neural progenitor regulation in the olfactory epithelium [61, 62] and for which increased DNAme (cg04816311) is associated with target organ damage in older African Americans [63]. Notably, mutations in the uncx orthologue in C. elegans, unc4 , extends male lifespan [64].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 ). Human UNCX encodes a homeobox transcription factor whose mouse homolog is implicated the development of the axial skeleton and in neural progenitor regulation in the olfactory epithelium [61, 62] and for which increased DNAme (cg04816311) is associated with target organ damage in older African Americans [63]. Notably, mutations in the uncx orthologue in C. elegans, unc4 , extends male lifespan [64].…”
Section: Resultsmentioning
confidence: 99%
“…In protostomes, Uncx function is largely restricted to the nervous system, where it specifies motor neuron identity, sometimes in a repeated, segmentally polarized fashion (Cho and Park, 2008; Lacin et al, 2020; Miller et al, 1992; Walthall, 1995). In contrast, the mammalian Unc-4 homolog Uncx4.1 serves as one of the best characterized posterior identity markers of the developing somites, where it instructs the formation of distal ribs, transverse processes and pedicles of the neural arches on vertebrae (Leitges et al, 2000; Mansouri et al ., 2000; Neidhardt et al, 1997; Schragle et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Uncx null mice show abnormal somitogenesis and then develop multiple axial skeletal malformations, including lordosis in the thoracic region, distorted ribs, fused ribs, split ossification center of the vertebral body, and loss of pedicles and transverse process. ( 26 ) The known function of Uncx in the axial skeletal development indicates the involvement of UNCX in the pathomechanism of AIS. In this study, we found that the risk allele of rs78148157 increased the UNCX expression, thus leading to further exploration of its effect of gain of function on the development of the spine.…”
Section: Discussionmentioning
confidence: 99%